Doppler Ultrasonography Of The Kidneys In Diabetic Patients - Mohamed Ahmed, Ala Mohammed Abd Elgyoum; Mohammed Jaber, Abd Allah; Elzaki, Amin A. E. (Asian Journal of Medical Radiological Research, 2012)
This study was conducted with an aim to assess the effect of diabetes on the kidneys using ultrasonography, specifically to assess the vascularty of kidneys by Doppler ultrasound in diabetic patients in Sudan. A total of forty seven samples of Sudanese diabetic patients between the mean of ages was 57.68 years were selected according to the positive evidence of diabetes. Features like patient shape, treatment taken, internal echogenicity, corticomedullary differentiation and renal artery indexes were employed.The examination of Doppler for 47patient showed that 93.6% of patients had ordinary renal artery resistance and 6.4% had high resistance. The study also showed that there were relations between the affection period of diabetic mellitus&changes happening in the kidneys such as renal failure 29.8%, pyelonephritis is 2.1%, renal artery stenosis 6.4%. The study proved that diabetic patients were subject to multiple changes in abdominal organs that can be diagnosed by ultrasound, this supports the use of ultrasound in diabetic treatment units.